Boosting the antibacterial potential of a linear encrypted peptide in a Kunitz-type inhibitor (ApTI) through physicochemical-guided approaches - Gutierrez, Camila de Oliveira; Almeida, Luís Henrique de Oliveira; Sardi, Janaina de Cássia Orlandi; Almeida, Claudiane Vilharroel; de Oliveira, Caio Fernando Ramalho; Marchetto, Reinaldo [UNESP]; Crusca, Edson [UNESP]; Buccini, Danieli Fernanda; Franco, Octavio Luiz; Cardoso, Marlon Henrique; Macedo, Maria Lígia Rodrigues (Elsevier, 2024)
Bacterial resistance has become a serious public health problem in recent years, thus encouraging the search for new antimicrobial agents. Here, we report an antimicrobial peptide (AMP), called PEPAD, which was designed based on an encrypted peptide from a Kunitz-type plant peptidase inhibitor. PEPAD was capable of rapidly inhibiting and eliminating numerous bacterial species at micromolar concentrations (from 4μM to 10 μM), with direct membrane activity. It was also observed that the peptide can act synergistically with ciprofloxacin and showed no toxicity in the G. mellonella in vivo assay. Circular dichroism assays revealed that the peptide's secondary structure adopts different scaffolds depending on the environment in which it is inserted. In lipids mimicking bacterial cell membranes, PEPAD adopts a more stable α-helical structure, which is consistent with its membrane-associated mechanism of action. When in contact with lipids mimicking mammalian cells, PEPAD adopts a disordered structure, losing its function and suggesting cellular selectivity. Therefore, these findings make PEPAD a promising candidate for future antimicrobial therapies with low toxicity to the host.
Keywords: Adenanthera pavonina; Antimicrobial peptide; Bacterial resistance; Encrypted peptides; Membrane selectivity